Electric spiking activity in epithelial cells - Sun-Min Yu; Steve Granick (Proceedings of the National Academy of Sciences, 2025)
Epithelial cells (human keratinocyte cells and the canine MDCK cell line), traditionally viewed as electrically non-self-excitable and involved primarily in physiological functions such as barrier presentation, absorption, secretion, and protection, are shown here to exhibit traveling extracellular electric charge when they recover from spatially focused, laser-induced wounding of confluent monolayers cultured on a multielectrode array chip. Voltage spikes measured on these electrodes display depolarization, repolarization, and hyperpolarization phases with amplitudes similar to the action potentials of neurons but with the markedly slower duration of 1 to 2 s. Some propagate distances up to hundreds of μm from the wound with a mean speed of around 10 mm s −1 . Generation and transmission of bioelectric signals are significantly influenced by the perturbation of mechanosensitive cationic ion channels. These direct measurements confirm bioelectric signaling that previous work has hypothesized to regulate epithelial cell development and may have relevance to the frequency parameter selection of bioelectric devices.